Cultural stereotyping of the lady in 4Q184 and 4Q185 - Geyser-Fouché, Ananda (HTS teologiese studies, 2016)
Wisdom and wickedness as a ‘Woman’ have always attracted much discussion, especially in the ways images of the female are employed in wisdom literature. This article focuses on two Qumran texts that fall into the category of wisdom literature, namely 4Q184 and 4Q185, and the metaphorical appropriation of the woman as a figure of wisdom or a figure of wickedness. By combining a number of traditions in certain forms, sages tried to establish an education for their learners on how to obtain wisdom with the ultimate purpose of creating harmony. The ultimate purpose of the wisdom teachings of the sages was to confirm the harmony in the universe, and these teachings were also conveyed to their learners. In their instructions, they often employed binary opposites such as ‘wise’ and ‘fool’ according to which someone was characterised, or rather stereotyped. The result of such binary stereotyping was that the ‘whore’ and the ‘holy one’ represented opposite poles, and became fixed images in Judaism. According to feminist exegetes, these images typify the concept of cultural stereotyping. This article aims to illustrate that two Qumran texts, 4Q184 and 4Q185, regarded as wisdom texts, employ the female stereotypes that were known in the wisdom literature of Judaism.